Features of pathogenesis and risk factors of in-hospital ischemic stroke - S. V. Kolomentsev; N. V. Tsygan; I. A. Voznyuk; S. N. Yanishevskiy; E. I. Shermatyuk; O. M. Ilyina; I. V. Litvinenko (Неврология, нейропсихиатрия, психосоматика)
In-hospital ischemic stroke (IHIS) is one of the most critical competing diseases that can develop in patients during inpatient treatment. Causes associated with diagnostic and therapeutic measures may play an additional role in the pathogenesis of IHIS, in addition to traditional risk factors.Objective: to study the pathogenesis features and assess risk factors for IHIS.Patients and methods. The comorbidity, main and additional risk factors of IHIS in patients of therapeutic (n=112; 44.3%), surgical (n=125; 49.4%) and neurological (n=16; 6.3%) profiles were studied.Results and discussion. The proportion of perioperative stroke in the study was 37.2%. The frequency of atherothrombotic, cardioembolic, and lacunar subtypes of IHIS did not differ in groups of patients of different profiles. In the group of surgical patients, the proportion of strokes of another established etiology was 24.8% and was higher than in therapeutic (9.8%; p<0.05) and neurological (6.25%; p<0.005) patients. The proportion of strokes of unknown etiology in the group of surgical patients, on the contrary, was lower (15.2%) than in patients with therapeutic (35.7%; p<0.05) and neurological (50.0%; p<0.05) profile. An additional risk factor for IHIS for non-surgical patients was insufficient antithrombotic prophylaxis, for surgical patients – surgery.Conclusion. Compared with out-of-hospital ischemic stroke, the causes of in-hospital ischemic stroke are more diverse and cannot always be explained solely by the higher comorbidity of hospitalized patients. The TOAST classification of ischemic stroke subtypes does not fully reflect the pathogenesis of IHIS, as it does not take into account the possibility of external influences, especially in cases where it is not possible to establish the exact cause of stroke, and the most likely trigger is medical intervention.